Non-native novice EFL teachers' beliefs about teaching and learning - Erkmen, Besime (2010)
This study investigated the beliefs about teaching and learning English of nine non-native novice teachers at a private university in Northern Cyprus, and the extent to which these beliefs changed in their first year of teaching. Data was collected over an academic year of nine months by means of semi-structured interviews, credos, classroom observations, post-lesson reflection forms, stimulated-recall interviews, diaries and a metaphor-elicitation task. The study found that novice teachers’ prior learning experiences were influential in shaping their initial beliefs. By the end of the year, change in the content of the teachers’ beliefs was limited. However, the findings also showed that the majority of the teachers’ beliefs were re-structured and strengthened, suggesting that beliefs are dynamic. Analysis of the findings indicated that several factors stimulated change in beliefs; differences in individual experiences; contextual factors i.e. the syllabus, dissatisfaction with student behaviour, and students’ expectations; and becoming aware of their beliefs and practices. Moreover, the study found that novice teachers’ beliefs were not always reflected in their teaching. The analysis showed that inconsistency between beliefs and practices resulted mainly from differences in individual experiences and the restriction of the syllabus. Thus, teachers were not always able to do what they believed would be effective in their classes. Based on the findings, the study argues that novice teachers are involved in a learning period in their first year of teaching and that their beliefs are susceptible to change. Implications of the findings are discussed in relation to teacher education programmes and recommendations are made for further research.